The causal relationship between 233 metabolites and coronary atherosclerosis: a Mendelian randomization study - Zhang, Hongwei; Zheng, Xiaoyu; Yan, Zian; Guo, Lijun; Zheng, Yuan; Zhang, Dawu; Ma, Xiaochang (Frontiers in Cardiovascular Medicine, 2024)
ObjectiveTo investigate the causal relationship between 233 newly reported metabolites and coronary atherosclerosis through Mendelian randomization analysis.MethodsFive different methods were used to perform Mendelian randomization analysis on the 233 metabolites and coronary atherosclerosis, with inverse variance weighting as the primary result, supplemented by other methods.ResultsThe analysis identified that certain metabolites increase the susceptibility risk of coronary atherosclerosis, including: Total fatty acids (OR = 1.40, 95% CI: 1.28–1.53, P < 0.001), Saturated fatty acids (OR = 1.44, 95% CI: 1.30–1.60, P < 0.001), Serum total triglyceride levels (OR = 1.33, 95% CI: 1.22–1.46, P < 0.001), Conjugated linoleic acid (OR = 1.16, 95% CI: 1.04–1.30, P = 0.007). Conversely, certain metabolites were found to reduce the occurrence of coronary atherosclerosis, such as: Cholesteryl esters to total lipids ratio in medium HDL (OR = 0.73, 95% CI: 0.67–0.78, P < 0.001), Cholesteryl esters to total lipids ratio in large HDL (OR = 0.64, 95% CI: 0.58–0.71, P < 0.001), Total cholesterol to total lipids ratio in medium HDL (OR = 0.71, 95% CI: 0.65–0.77, P < 0.001).ConclusionThere is a close relationship between metabolites and the occurrence of coronary atherosclerosis. This study conducted Mendelian randomization analysis on the causal relationship between 233 metabolites and coronary atherosclerosis, providing potential new insights for the treatment of this disease.